Determining The Critical Degree of Reservoir Lifetime for The Saguling Reservoir Based on The Sediment Inflow Simulation - Bakhtiar, Bakhtiar; Hadihardaja, Joetata; Hadihardaja, Iwan K. (Institut Teknologi Bandung, 2010)
Abstract. This study aims to find out the relationship between the critical degree of reservoir lifetime and sediment inflow. The critical degree of reservoir lifetime is defined as the ratio between the designated lifetime of the reservoir and its effective lifetime. The effective lifetime of a reservoir is affected by the amount of sediment flowing into the reservoir and trap efficiency. Soil and Water Assessment Tool (SWAT) version 2005 model was incorporated into this study to simulate hydrological processes taking place in the catchment. The reliability of of SWATmodel depends greatly on the data availability and some parameter adjustments. From the calibration and validation results on monthly data, the model is considerably of good performance. TheÂ modeling resultsrevealed that the mean sediment yield is 235.86 ton/ha/year, and the mean sediment inflow into the reservoir is 5,102,000 tons per year which is equivalent to 3,836,090 m3 per year resulting in 43.66 years of the reservoir lifetime (21.66 years remaining) which corresponds to the critical degree of 2.29 The graph plotting the values of the sediment inflow and the critical degree of reservoir lifetime reveals a linear relationship. Abstrak. Penelitian ini dimaksudkan untuk mencari hubungan antara tingkat kekritisan umur waduk dengan inflow sedimen. Tingkat kekritisan umur waduk didefinisikan sebagai perbandingan antara umur rencana waduk dengan umur efektifnya. Umur efektif waduk dipengaruhi oleh jumlah sedimen yang masuk ke waduk serta efisiensi pengendapan sedimen. Model Soil and Water Assessment Tool (SWAT) versi 2005 digunakan dalam penelitian ini untuk mensimulasikan proses-proses hidrologi yang terjadi di daerah tangkapan. Keandalan model SWAT sangat bergantung pada ketersediaan data dan penyesuaian beberapa parameter. Dari hasil kalibrasi dan validasi terhadap data bulanan, kinerja model dinilai cukup baik. Hasil simulasi menunjukkan bahwa sediment yield rata-rata sebesar 235,86 ton/ha/tahun, serta inflow sedimen rata-rata yang masuk ke waduk sebesar 5.102.000 ton per tahun yang ekivalen dengan 3.836.090 m3 per tahun yang menghasilkan umur waduk sebesar 43,66 tahun (21,66 sisa umur waduk) yang bersesuaian dengan tingkat kekritisan 2,29. Grafik yang menghubungan nilai inflow sedimen dengan tingkat kekritisan umur waduk menunjukkan hubungan yang bersifat linear.